Предмет: Алгебра, автор: Funchosa

помогите пожалуйста ​

Приложения:

Ответы

Автор ответа: darkness88lucifer
1

Ответ:

(2 - 1)(2 + 1) =  {2}^{2}  - 1 \\ ( {2}^{2}  - 1)( {2}^{2}  + 1) =  {2}^{4}  - 1 \\ ( {2}^{4} - 1)( {2}^{4}   + 1) =  {2}^{8}  - 1 \\ ( {2}^{8}  - 1)( {2}^{8}  + 1) =  {2}^{16}  - 1 \\  {2}^{16}  - 1 -  {2}^{16}  =  - 1

 - 2.62 \times 5.31 +  {5.31}^{2}  +  {1.31}^{2}  =  {5.31}^{2}  - 2 \times 1.31 \times 5.31 +  {1.31}^{2}  =  {(5.31 - 1.31)}^{2}  =  {4}^{2}  = 16


Funchosa: спасибо)
Похожие вопросы
Предмет: Русский язык, автор: Lol228m1
Предмет: География, автор: twiceerlanbaibazarov